A cyclic voltammetric study of the influence of supporting electrolytes on the redox behaviour of Cu(II) in aqueous medium (Journal of the Bangladesh Chemical Society, 2012)
The electrochemical redox behavior of Cu(II) has been investigated at glassy carbon electrode (GCE) in Britton-Robinson (BR) buffer as well as in a mixture of BR buffer and potassium chloride media. It is apparent that BR buffer can act as a supporting electrolyte and modify the electrochemical behavior of Cu(II) ion in aqueous medium. In BR buffer medium, Cu(II) undergoes one two-electrons redox process, while in a mixture of BR buffer and KCl media it follows two one-electron electrochemical reaction routes. Because of the formation of hydrogen bridge bond between the supporting electrolyte and GCE surface, the Cu(II) ion follows Cu(II)/Cu(0) electrochemical reaction path, while in presence of KCl such a hydrogen bridge bond is not formed and it undergoes successive Cu(II)/Cu(I) and Cu(I)/Cu(0) electrode reaction processes. Moreover, the linear variation of peak current with the square root of scan rate indicates that the electrochemical redox processes are diffusion controlled. Keywords: Supporting electrolytes; Britton-Robinson buffer; Cu-reduction; Peak current DOI: http://dx.doi.org/10.3329/jbcs.v24i2.9704 Journal of Bangladesh Chemical Society, Vol. 24(2), 158-164, 2011